Design and Analysis of Control Systems Case Studies - Stein Shiromoto, Humberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides methods to unify different approaches to tackle stability theory problems. In particular, it presents a methodology to blend approaches obtained from measure theory with methods obtained from Lyapunov's stability theory. The author summarizes recent works on how different analysis/design methods can be unified and employed for systems that do not belong to either of domains of validity.
Keywords: Engineering mathematics; Engineering -- Data processing; Control engineering; Robotics; Automation; Nonlinear Optics; Mathematical and Computational Engineering Applications; Control, Robotics, Automation; Nonlinear Optics